1993
DOI: 10.1111/j.1365-2842.1993.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel surface roughness analysis after laser ablation and acid‐etching

Abstract: Laser-roughened enamel surfaces have been shown to provide for greater acid-resistance and enhanced restorative material/enamel bond strength. Extracted tooth enamel was irradiated with several lasers: CO2/Nd:YAG (CW), CO2 (RSP), Nd:YAG (CW), Nd:YAG (Q-switched), Argon (CW), and Ar:F excimer. Additional teeth were acid-etched. Energy densities were standardized at 25.47 J/cm2 for all mediums. Surface profile analyses were conducted with a profilometer to determine the amount of enamel surface roughness. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 25 publications
1
27
0
3
Order By: Relevance
“…Studies have shown that changes in the morphology of enamel/dentin surfaces after laser irradiation are similar to those produced in acid-etched specimens [Hess, 1990;Arcoria et al, 1993]. The potential use of lasers as an alternative to acid etching has resulted in extensive composite-resin bonding studies with CO 2 and Nd-YAG lasers [Liberman et al, 1984;Cooper et al, 1988;von Fraunhofer et al, 1993].…”
mentioning
confidence: 99%
“…Studies have shown that changes in the morphology of enamel/dentin surfaces after laser irradiation are similar to those produced in acid-etched specimens [Hess, 1990;Arcoria et al, 1993]. The potential use of lasers as an alternative to acid etching has resulted in extensive composite-resin bonding studies with CO 2 and Nd-YAG lasers [Liberman et al, 1984;Cooper et al, 1988;von Fraunhofer et al, 1993].…”
mentioning
confidence: 99%
“…With the advent of dental lasers, the effects of these devices on surface treatment of enamel have been investigated, and laser ablation has become an alternative to acid etching. 21 Research has shown that laser irradiation produces an amount of surface roughness comparable 22 or similar 23 to that seen with acid etching. Er:YAG laser conditioning has been proven effective for hard-tissue ablation without thermal side effects.…”
Section: Discussionmentioning
confidence: 90%
“…Technological advances during the last decade have resulted in the increased use of lasers in dentistry. Many of these advances have been directed at the use of lasers in clinical applications as an alternative to acid etching of enamel or dentin for bonding dental materials to the tooth surface (Arcoria et al 1993). However, the use of lasers in dental material processing has been limited (Akova et al 2008).…”
Section: Onementioning
confidence: 99%